Indonesia’s Foreign Policy on Palestine and the Rohingya: Affective Solidarity and Strategic Ambivalence - Prabandari, Atin; Darmawan, Arief Bakhtiar (Department of International Relations, Faculty of Social and Political Science, Universitas Airlangga, 2026)
Indonesia’s foreign policy has long carried a language of solidarity, especially toward oppressed Muslim communities such as the Palestinians and the Rohingya. While existing scholarship tends to explain Indonesia’s foreign policy through normative, religious, or strategic orientations, it has largely neglected the role of emotions in shaping foreign policy orientation. The article employs a post-positivist analytical lens—Affective Foreign Policy Analysis—to examine Indonesia's emotions in two case studies: the Palestinian Case and the Rohingya Crisis. The emotions considered are solidarity, compassion, pride, and ambivalence. In the Palestinian case, Indonesia has consistently taken a firm stance, drawing on its own parallelism and the emotional resonance of Islamic solidarity. In contrast, Indonesia has displayed a more ambivalent stand over the Rohingya crisis: strong affective mobilization at the societal level and yet restrained and selective humanitarianism at the state level, limited by sovereignty concerns and Indonesia’s non-signatory status to the 1951 Refugee Convention. Through comparative case studies analysis, the article argues that emotions sustain Indonesia’s foreign policy discourse while exposing gaps between solidarity and strategy within institutional constraints. The article concludes that understanding Global South foreign policy requires taking the role of emotions seriously as central mediators between ideals and interests. Keywords: Indonesia’s foreign policy, Palestine, Rohingya, Affective solidarity, Strategic ambivalence. Kajian yang ada kerap merasionalisasi kebijakan luar negeri Indonesia dengan komitmen normatif, identitas agama, atau kepentingan strategis pragmatisnya, pembahasan terhadap peran emosi dalam membatasi pilihan nasional masih terlalu minim. Artikel ini menggunakan lensa analitis pasca-positivis—analisis kebijakan luar negeri afektif—untuk membaca emosi dalam tanggapan Indonesia terhadap dua studi kasus, yaitu Palestina dan krisis Rohingya. Ada perbedaan sikap yang ditunjukkan Indonesia dalam kasus Palestina, lantaran adanya emosi yang bersifat paralel dan menggetarkan solidaritas Islam. Sebaliknya, Indonesia cenderung ambivalen terhadap krisis Rohingya. Melalui analisis komparatif, artikel ini berasumsi bahwa emosi dapat menjadi pendorong kuat bagi narasi kebijakan luar negeri Indonesia, sekaligus mengungkap kesenjangan antara solidaritas dan strategi dalam batasan kelembagaan. Artikel ini menyimpulkan bahwa dalam memahami kebijakan luar negeri Selatan-Selatan, diperlukan tanggapan serius terhadap emosi sebagai mediator utama antara cita-cita dan kepentingan. Kata-kata Kunci: Kebijakan luar negeri Indonesia, Palestina, Rohingya, Solidaritas afektif, Ambivalensi strategis.